Development of Triple Representation Based on Virtual Laboratory Media on the Chemical Equilibrium Experiment in Online Learning Era - Deni Ainur Rokhim; Maya Oki Septiani (Chemistry Education Department, 2021)
The purpose of this research is to produce virtual laboratory media to support laboratory-based learning with the features mentioned above to make students become scientists with comprehensive understanding competencies and laboratory engineering skills. The virtual laboratory media was developed using the Lee Owens development method consists of five stages: analysis, design, development, implementation, and evaluation. The virtual laboratory based on triplet representations on chemical equilibrium material fulfils very feasible criteria for students to use as a learning resource. The percentage of product eligibility as a learning media is 86.15%, and in terms of the material, it is 85.71%. The results of small group trials in class XI students of SMAN 3 Sidoarjo showed that the virtual laboratory developed had met the very feasible criteria with an average percentage of 86.40%. The final result of this virtual laboratory has been revised based on comments and suggestions from validators and test subjects. Practically, the media developed is very useful to support practicum learning.